THE RELATIONSHIP OF THE BODY MASS INDEX AND WAIST CIRCUMFERENCE WITH BLOOD PRESSURE AT KARANG ASAM PUBLIC HEALTH CENTER SAMARINDA - Syella Chintya Dewi; Muhammad Furqon; Danial Danial (Universitas Muhammadiyah Kalimantan Timur, 2019)
Hypertension is the most common cause of cardiovascular disease and it is a major problem in both developed and developing countries. Obesity is one of the main risk factors of hypertension. Hypertension and obesity are health problems which its prevalence is continues to increase in Indonesia. The anthropometric index that can be used to determine nutritional status are the body mass index (BMI) and waist circumference measurement. This study was an observational analytic with cross sectional method. The sample of this study was 275 respondent who were selected using the consecutive sampling method in Karang Asam public health center Samarinda. Data of this study were obtained from direct measurement of height, weight, waist circumference and blood pressure of respondent and data were analyzed by using chi square test. The result of statistical test showed that there was relationship between body mass index (p = 0,000 ; OR= 5,234 ; 95% CI= 3,090-8,865) and waist circumference (p = 0,000; OR=5,489 ; 95% CI= 3,233 – 9,318) with blood pressure. There was a significant relationship between body mass index and waist circumference with blood pressure at Karang Asam Public Health Center Samarinda.